Sociodemographic profile, clinical presentations, environmental factors, and laboratory parameters of dengue patients: A retrospective study from Mizoram, India - Varte, Zorinsangi; Sailo, Lalnuntluanga; John Lalliandinga Tochhong,; Lalruatsanga, David; Zothantluanga,; Hnamte, Lalrinmawia; Anusuya, Ganesh Shanmugasundaram (Asian Journal of Medical Sciences, 2023)
Background: Mizoram is one of the states in India with high cases of dengue for the year 2022. There is very limited data regarding the sociodemographic profile, clinical presentation, environmental factors, and laboratory parameters and outcome of infection of dengue patients in Mizoram. Aims and Objectives: The present study was aimed to study factors and the proportion of patients getting admitted with dengue fever (DF), DF with warning signs and severe dengue. Materials and Methods: The data collected retrospectively from the medical records of the patients admitted in three private hospitals and two governmental hospitals during the time period from July to November 2022. Descriptive analysis was carried out and categorical outcomes were compared between study groups using Chi-square/Fisher’s Exact test. Mean values were compared between study groups using ANOVA (>2 groups). P<0.05 was considered statistically significant. Results: Out of 189 patients, 103 (54.50%) were male and majority were aged >14 years 166 (87.83%). Mean age was 42.08. Majority 157 (83.07%) belonged to urban population. DF were 137 (72.49%), severe dengue 10 (5.29%), and with warning signs of severe dengue 42 (22.22%). Most common symptoms observed were fever 181 (95.77%) followed by myalgia 95 (50.26%). Severe dengue was reported more among females 7 (70%), DF was more common among males 71 (51.82%) (P=0.041). DF was more common in patients from urban 113 (82.48%) versus rural 24 (17.52%) (P<0.001). Mortality was 1.59%. Conclusion: Health education and integrated vector control measures need to be intensified to prevent future dengue outbreaks in Mizoram.